Developing serious games with the APEX framework - Gomes, Tiago Emanuel Oliveira (2013)
APEX was developed as a framework for the prototyping of ubiquitous computing (ubicomp) environments. In this paper we explore its role as a platform for developing serious games. In particular we describe the Asthma game which is aimed at raising awareness of Asthma triggers among children. The game is designed to stimulate a healthier life-style for children with ashma.